Research and Clinical Application of Three-Dimensional Location of Amygdaloid Body. Issue 6 (September 2017) - Duan, Haobo; Shang, Pei; Bai, Peng; Li, Zilu; Li, Youqiong; Cheng, Kailiang; Xin, Meiying
Abstract : Abstract: Accurately representing the spatial location of the amygdaloid body can lay an anatomical basis for the neurosurgery operation for amputation of the amygdaloid body through lateral fissure approach. As we know, there are a number of nerve nucleuses and essential structures locating around amygdaloid body in our brain, especially optic tract. However, only few research had been done to protect these tissues or nerve nucleuses. Thus, we reconstructed the three-dimensional images of the amygdaloid body of the human brain and established a coordinate system. The morphological parameters of the amygdaloid body and the three-dimensional coordinate data were measured. The spherical coordinates (R, θ, φ) were constructed by calculating the azimuth angle, elevation angle, and the distance from the coordinates origin to each amygdaloid body centroid. Sixty people brain MRI images without any visible organic disease were used in our research to investigate the average level of related parameters. The authors selected a proper coordinate origin and measured the value of anteroposterior diameter, right-and-left diameter, vertical diameter of the amygdaloid body, and the distance from the optic tract to amygdaloid body. The authors also measured the three-dimensional coordinate data of each centroid of the amygdaloid body in order to provide anatomical suggestion for surgery. The authors confirmed the nearest point from the foremost edge of the brain ventricle temporal horn to the lateral fissure, then viewed it as the coordinate origin. By means of coordinate translation, the authors got various morphological parameters and the coordinate values of each centroid of the amygdaloid body. Spherical coordinates were calculated from the three-dimensional coordinate values. The distances between the different layers of the amygdaloid body and the optic tract were also measured. The reconstruction of the three-dimensional coordinates of amygdaloid body is part of the digital engineering of the human body. The measurement of the parameters provides an important theoretical basis for the clinical amygdaloid body destruction surgery. Finally, the authors get conclusions as follows. There are no significant differences in the measured values of r1, r2, and r3 between the upper and lower diameters, the left and right diameters, the anteroposterior diameter of the amygdaloid body. The measured values of men and women are not statistically significant ( P > 0.05). Spherical coordinates (R, θ, φ) calculated from the three-dimensional coordinate values and values from different sexes of the amygdaloid body are not statistically significant, either ( P > 0.05). The distance between the different levels of the amygdaloid body and the optic tract (h1, h2, h3, h4, h5, h6, and h7) are not statistically significant ( P > 0.05).